High-stress-corrosion-resistant Al-Cu-Mg alloy and preparation method and application of thick plate of high-stress-corrosion-resistant Al-Cu-Mg alloy
By optimizing the composition and process of Al-Cu-Mg alloy, controlling its microstructure characteristics and precipitation phases, the stress corrosion problem of the alloy in high-stress environments is solved, and the excellent stress corrosion resistance and low-cost and efficient process of alloy thick plates for aerospace are achieved.
Patent Information
- Application Number
- CN202411458739.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-28
AI Technical Summary
The existing Al-Cu-Mg alloys are prone to stress corrosion cracking under high stress environments, which is difficult to meet the strict requirements for stress corrosion resistance in the aerospace field.
By optimizing the Cu and Mg content of the main alloy elements, controlling the reasonable matching of the Mn content of the microalloy elements with the rolling temperature, regulating the microstructure characteristics and precipitation phase morphology and distribution, the Al-Cu-Mg alloy thick plate with excellent stress corrosion resistance was prepared by using the processes of ingot homogenization, hot rolling, double-stage solid solution treatment, pre-stretching and cold deformation and artificial aging treatment.
The excellent stress corrosion resistance of Al-Cu-Mg alloy thick plate under high stress conditions is achieved, which meets the performance requirements of aerospace equipment, while reducing production costs and simplifying the process flow.
Smart Images

Figure CN119530622A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, and in particular to an Al-Cu-Mg alloy resistant to high stress corrosion and a preparation method and application of a thick plate thereof. Background Art
[0002] Al-Cu-Mg alloys are often used to manufacture integral, large-section aircraft main load-bearing structures and pressure-bearing components due to their high specific strength, good fracture toughness and fatigue performance, good heat resistance and excellent processing performance. With the rapid development of the aerospace industry, more stringent requirements have been put forward for high-performance aluminum alloys. In terms of corrosion, aluminum alloy materials are required to be guaranteed not to suffer from stress corrosion cracking when serving in different stress environments. How to ensure that Al-Cu-Mg alloys still have excellent stress corrosion resistance in high-stress environments is a key technical issue in the research and promotion of aluminum alloys.
[0003] The chemical distribution between the grain boundary and the bulk phase of Al-Cu-Mg alloy after heat treatment will lead to significant differences in local electrochemical and mechanical behaviors. These differences will lead to a serious reduction in the ability of the grain boundary to resist intergranular fracture damage. The precipitated phase distributed along the grain boundary may be a potential location for crack initiation, leading to intergranular fracture and stress corrosion cracking. In order to improve the stress corrosion resistance of Al-Cu-Mg alloy, the alloy composition is generally optimized and the heat treatment process is adjusted to change the morphology and distribution of the precipitated phase within the grain and the precipitated phase at the grain boundary, so that the alloy can obtain excellent stress corrosion resistance. In addition, due to the high large-angle energy, it is easy to provide nucleation sites for the precipitation of the grain boundary phase, and stress corrosion cracking is prone to occur under service environment. Regulating the organizational characteristics and obtaining a high-density subgrained structure are also the main means to improve the stress corrosion resistance of aluminum alloys.
[0004] At present, there are related patent reports on the method of improving the corrosion performance of Al-Cu-Mg alloy. For example, patent CN114752831B discloses a high-strength corrosion-resistant aluminum alloy and its preparation method and application. By controlling the Cu / Mg ratio and Cu / Zn ratio, combined with the three-stage cooling process of the melting and casting process, the corrosion resistance of the alloy is improved without reducing the mechanical properties of the alloy. The patent achieves the purpose of improving intergranular corrosion and exfoliation corrosion performance by controlling the alloy element ratio, but does not involve corrosion performance under high stress. Patent CN108118273B discloses a method for improving the corrosion resistance of aluminum alloys. The treatment process of cold deformation + first-level aging + cold deformation + second-level aging is used for 2XXX series and 7XXX series high-strength aluminum alloys. By adjusting the cold deformation amount and combining the aging treatment process, the stress corrosion resistance of the alloy is improved. The patent adopts a process of increasing cold deformation before double-stage aging to improve stress corrosion performance, but the cold deformation of thick plates has high requirements on equipment, and the process is complicated and difficult to operate. Therefore, the method for improving the corrosion resistance of aluminum alloys disclosed in the patent is not suitable for thick plates. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention optimizes the content and ratio of the main alloying elements Cu and Mg, controls the content of the microalloying element Mn and the rolling temperature to reasonably match, and regulates the microstructure characteristics and the morphology and distribution of the precipitated phase. Specifically, an Al-Cu-Mg alloy resistant to high stress corrosion and a thick plate preparation method and application thereof are proposed for Al-Cu-Mg alloy thick plates for aerospace use. The Al-Cu-Mg alloy thick plate described in the present invention has excellent stress corrosion resistance under high stress conditions, and has low production costs and a simple process flow, and excellent stress corrosion resistance can be obtained under existing preparation conditions. The present invention specifically includes the following contents:
[0006] An Al-Cu-Mg alloy resistant to high stress corrosion comprises the following components and weight percentages: Cu 4.0-4.6%, Mg 1.4-1.6%, Mn 0.3-0.9%, Cr≤0.06%, Ti≤0.03%, Fe≤0.05%, Si≤0.03%, the total amount of impurity elements is less than 0.15%, and the balance is Al, wherein the Cu / Mg ratio is not greater than 3.
[0007] A method for preparing a high stress corrosion resistant Al-Cu-Mg alloy thick plate, using an ingot of the Al-Cu-Mg alloy with the above composition and content as a raw material for making the thick plate;
[0008] S1: homogenizing the aluminum alloy ingot at a homogenization temperature of 505-510°C;
[0009] S2: hot rolling the homogenized ingot to obtain a plate, when the Mn content of the alloy is less than or equal to 0.6%, the initial rolling temperature T1 is 460°C≤T1≤480°C; when the Mn content of the alloy is greater than 0.6%, the initial rolling temperature T2 is 480°C<T2≤500°C, and the final rolling temperature is greater than 380°C; the total rolling deformation is 75-90%, and the deformation of each pass during the rolling process is 5-25%;
[0010] S3: performing a two-stage solid solution treatment on the hot-rolled plate, and quenching to room temperature after the solid solution treatment to obtain a solid solution state plate;
[0011] S4: pre-stretching and cold-deforming the solid solution plate to reduce the residual stress of the plate;
[0012] S5: The cold-deformed plate is artificially aged within 30 days. The heating rate of the aging treatment is 10-20°C / h, the insulation temperature is 200-220°C, and the insulation time is 10-15h. The final plate conductivity is not less than 41% IACS, and finally an Al-Cu-Mg alloy thick plate resistant to high stress corrosion is obtained.
[0013] Specifically, the holding time of the ingot homogenization treatment in step S1 is 24-48 hours.
[0014] Specifically, the rolling speed in step S2 is 50-100 m / min.
[0015] Specifically, the process of the double-stage solution treatment described in step S3 is: heating from room temperature to 480-490°C at a heating rate of 25-50°C / h, keeping warm for 0.5-1h, then heating to 500-505°C at a heating rate of 10-20°C / h, keeping warm for 1-2h.
[0016] Specifically, the recrystallization area of the solid solution state plate obtained in step S3 is less than 20%, and the subgrain boundary density is 100-200 mm / mm 2 .
[0017] An Al-Cu-Mg alloy thick plate resistant to high stress corrosion prepared by the preparation method.
[0018] Specifically, the Al-Cu-Mg alloy thick plate resistant to high stress corrosion has a tensile strength of not less than 475 MPa, a yield strength of not less than 415 MPa, an elongation of not less than 10%, and does not crack after cyclic infiltration for 30 days under a stress condition of 370 MPa in accordance with GB / T 22640-2008 Stress Corrosion Test Method for C Ring Specimens of Aluminum Alloy Processing Products.
[0019] An application of the above-mentioned Al-Cu-Mg alloy thick plate resistant to high stress corrosion in aerospace equipment.
[0020] The present invention has the following beneficial effects:
[0021] (1) The aluminum alloy thick plate of the present invention optimizes the content and ratio of the main alloying elements Cu and Mg, thereby ensuring the precipitation of high-density Al2Cu phase and Al2CuMg phase in the grain, thereby ensuring that the aluminum alloy has high strength; and regulates the element content of the Al2CuMg phase at the grain boundary, thereby reducing the potential difference between the grain boundary phase and the aluminum matrix near the grain boundary, inhibiting the generation of electrochemical reactions at the grain boundary, thereby improving the stress corrosion resistance of the Al-Cu-Mg alloy.
[0022] (2) The aluminum alloy thick plate of the present invention controls the reasonable matching of the microalloying element Mn content and the rolling temperature, and regulates the recrystallization process of the plate during hot rolling and solid solution stages, so that the final plate obtains microstructure characteristics with excellent stress corrosion resistance, including a higher density of subgrain structures and a lower degree of recrystallization.
[0023] (3) The aluminum alloy thick plate of the present invention optimizes the characteristics of the intragranular and grain boundary precipitation phases by controlling the content and ratio of the main alloying elements and reasonably matching them with the over-aging treatment process. The intragranular precipitation phase is fine and dispersed, and the grain boundary precipitation phase is discontinuously distributed, thereby achieving excellent stress corrosion resistance while ensuring the strength of the plate.
[0024] (4) The aluminum alloy thick plate of the present invention has a tensile strength of not less than 475 MPa, a yield strength of not less than 415 MPa, and an elongation of not less than 10% in the rolling direction. According to GB / T 22640-2008 Stress Corrosion Test Method for C Ring Specimens of Aluminum Alloy Processing Products, it does not crack after 30 days of periodic infiltration under a stress of 370 MPa, thus meeting the performance requirements of aluminum alloys for aviation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0026] Figure 1 The homogenized structure of the Al-Cu-Mg alloy ingot in Example 1 of the present invention;
[0027] Figure 2 The grain structure of the Al-Cu-Mg alloy thick plate in Example 1 of the present invention;
[0028] Figure 3 The grain structure of the Al-Cu-Mg alloy thick plate in Example 2 of the present invention;
[0029] Figure 4 TEM structure of the precipitation phase in the Al-Cu-Mg alloy thick plate in Example 3 of the present invention;
[0030] Figure 5 TEM structure of the grain boundary precipitation phase of the Al-Cu-Mg alloy thick plate in Example 4 of the present invention;
[0031] Figure 6 The C-ring fracture of the Al-Cu-Mg alloy thick plate in Example 5 of the present invention;
[0032] Figure 7 The C-ring fracture of the Al-Cu-Mg alloy thick plate in Example 6 of the present invention;
[0033] Figure 8 The grain structure of the Al-Cu-Mg alloy thick plate in Comparative Example 2 of the present invention;
[0034] Fig. 9 This is the C-ring fracture of the Al-Cu-Mg alloy thick plate in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] The invention discloses a method for preparing a thick Al-Cu-Mg alloy plate resistant to high stress corrosion, comprising the following steps: using an aluminum alloy ingot as a raw material for making the thick plate, wherein the composition and weight percentage of the aluminum alloy ingot are: Cu 4.0-4.6%, Mg 1.4-1.6%, Mn 0.3-0.9%, Cr≤0.06%, Ti≤0.03%, Fe≤0.05%, Si≤0.03%, the total amount of impurity elements is less than 0.15%, the balance is Al, and the Cu / Mg ratio is not greater than 3; S1: homogenizing the aluminum alloy ingot, and the homogenizing temperature is 505-510°C; S2: hot rolling the ingot after the homogenization treatment to obtain a plate, and when the Mn content of the alloy is less than or equal to 0.6%, the initial rolling temperature T1 is 460 ℃≤T1≤480℃; when the Mn content of the alloy is greater than 0.6%, the initial rolling temperature T2 is 480℃<T2≤500℃, and the final rolling temperature is greater than 380℃; the total rolling deformation is 75-90%, and the deformation of each pass during the rolling process is 5-25%; S3: the hot-rolled plate is subjected to a two-stage solid solution treatment, and after the solid solution treatment is completed, it is quenched to room temperature to obtain a solid solution state plate; S4: the solid solution state plate is subjected to pre-stretching cold deformation to reduce the residual stress of the plate;
[0037] S5: The cold-deformed plate is artificially aged within 30 days. The heating rate of the aging treatment is 10-20°C / h, the insulation temperature is 200-220°C, and the insulation time is 10-15h. The final plate conductivity is not less than 41% IACS, and finally an Al-Cu-Mg alloy thick plate resistant to high stress corrosion is obtained.
[0038] The principles followed by the above implementation methods are: (1) The aluminum alloy thick plate of the present invention optimizes the content and ratio of the main alloying elements Cu and Mg, thereby ensuring the precipitation of high-density Al2Cu phase and Al2CuMg phase in the grain, thereby ensuring that the aluminum alloy has high strength; and regulates the element content of the Al2CuMg phase at the grain boundary, thereby reducing the potential difference between the grain boundary phase and the aluminum matrix near the grain boundary, inhibiting the generation of electrochemical reactions at the grain boundary, thereby improving the stress corrosion resistance of the Al-Cu-Mg alloy; (2) The aluminum alloy thick plate of the present invention controls the microalloying The reasonable matching of the Mn content and the rolling temperature regulates the recrystallization process of the plate in the hot rolling and solid solution stages, so that the final plate obtains microstructure characteristics with excellent stress corrosion resistance, including a higher density of subgrain structures and a lower degree of recrystallization; (3) The aluminum alloy thick plate of the present invention optimizes the characteristics of the intragranular and grain boundary precipitation phases by controlling the content and ratio of the main alloying elements and the reasonable matching of the over-aging treatment process. The intragranular precipitation phase is fine and dispersed, and the grain boundary precipitation phase is discontinuously distributed, thereby ensuring the strength of the plate while obtaining excellent stress corrosion resistance.
[0039] By adopting the method disclosed in the present invention, an Al-Cu-Mg alloy thick plate resistant to high stress corrosion is finally obtained. The tensile strength of the Al-Cu-Mg alloy thick plate resistant to high stress corrosion is not less than 475MPa, the yield strength is not less than 415MPa, the elongation is not less than 10%, and the electrical conductivity is not less than 41%IACS. According to "GB / T 22640-2008 C ring specimen stress corrosion test method for aluminum alloy processed products", it does not crack after periodic infiltration for 30 days under the stress condition of 370MPa, and meets the performance requirements of aluminum alloy thick plates for aerospace.
[0040] The specific steps of the preparation method are as follows:
[0041] Aluminum alloy ingots are used as raw materials for making thick plates. The components and weight percentages of the aluminum alloy ingots are: Cu 4.0-4.6%, Mg 1.4-1.6%, Mn 0.3-0.9%, Cr≤0.06%, Ti≤0.03%, Fe≤0.05%, Si≤0.03%, the total amount of impurity elements is less than 0.15%, and the balance is Al, wherein the Cu / Mg ratio is not greater than 3; specifically, the Cu content in the alloy can be 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, etc.; the Mg content can be 1.4%, 1.45%, 1.5%, 1.55%, 1.6%, etc.; the Mn content can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, etc. ; The Cr content can be 0, 0.01%, 0.02%, 0.03%, 0.40%, 0.05%, etc.; the Ti content can be 0, 0.01%, 0.02%, 0.03%, etc.; the Fe content can be 0, 0.01%, 0.02%, 0.03%, 0.40%, 0.05%, etc.; the Si content can be 0, 0.01%, 0.02%, 0.03%, etc.; the total impurity content can be 0.06%, 0.08%, 0.10%, 0.12%, 0.14%, etc.; the Cu / Mg ratio can be 2.5, 2.6, 2.7, 2.8, 2.9, 3, etc.
[0042] S1: homogenizing the aluminum alloy ingot, the homogenizing temperature is 505-510°C (for example, 505°C, 506°C, 507°C, 508°C, 509°C, 510°C, etc.), and the holding time is 24-48h (for example, 24h, 30h, 36h, 42h, 48h, etc.);
[0043] S2: The ingot after homogenization treatment is hot rolled to obtain a plate. When the Mn content of the alloy is less than or equal to 0.6%, the initial rolling temperature T1 is 460℃≤T1≤480℃; when the Mn content of the alloy is greater than 0.6%, the initial rolling temperature T2 is 480℃<T2≤500℃, and the final rolling temperature is greater than 380℃; specifically, when the Mn content of the alloy is 0.4, 0.45, 0.5, 0.55 , 0.6%, etc., the initial rolling temperature can be 460℃, 464℃, 468℃, 472℃, 476℃, 480℃, etc.; when the Mn content of the alloy is 0.65, 0.7, 0.75, 0.8%, etc., the initial rolling temperature can be 484℃, 488℃, 492℃, 496℃, 500℃, etc.; the final rolling temperature can be 383℃, 386℃, 388℃, 390℃, etc. The total rolling deformation is 75-90% (e.g. 75%, 78%, 82%, 85%, 88%, 90%, etc.), the deformation of each pass in the rolling process is 5-25% (e.g. 5%, 10%, 15%, 20%, 25%, etc.), and the rolling speed is 50-100m / min (e.g. 50m / min, 60m / min, 70m / min, 80m / min, 90m / min, 100m / min, etc.);
[0044] S3: The hot rolled plate is subjected to a two-stage solution treatment, wherein the solution treatment process is as follows: heating from room temperature to 480-490°C (e.g., 482°C, 484°C, 486°C, 488°C, 490°C, etc.) at a heating rate of 25-50°C / h (e.g., 25°C / h, 30°C / h, 35°C / h, 40°C / h, 45°C / h, 50°C / h, etc.), keeping the temperature for 0.5-1h (e.g., 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, etc.), and then heating at 10-20°C / h (e.g., 10°C / h, 12°C / h, The plate is heated to 500-505°C (e.g., 500°C, 501°C, 502°C, 503°C, 504°C, 505°C, etc.) at a heating rate of 14°C / h, 16°C / h, 18°C / h, 20°C / h, etc.), and kept warm for 1-2h (e.g., 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, etc.). After the solution treatment is completed, the plate is quenched to room temperature, and the recrystallization area of the obtained solution state plate is less than 20% (e.g., 4%, 6%, 8%, 10%, 13%, 17%, 19%, etc.), and the subgrain boundary density is 100-200mm / mm 2 (e.g. 100mm / mm 2 , 120mm / mm 2 , 135mm / mm 2 , 155mm / mm 2 , 175mm / mm 2 , 200mm / mm 2wait);
[0045] S4: pre-stretching and cold-deforming the solid solution plate to reduce the residual stress of the plate;
[0046] S5: The cold-deformed plate is artificially aged within 30 days, the heating rate of the aging treatment is 10-20°C / h (for example, 12°C / h, 14°C / h, 16°C / h, 18°C / h, 20°C / h, etc.), the holding temperature is 200-220°C (for example, 200°C, 205°C, 210°C, 215°C, 220°C, etc.), the holding time is 10-15h (for example, 10h, 11h, 12h, 13h, 14h, 15h, etc.), and the electrical conductivity of the final plate is not less than 41% IACS (for example, 41% IACS, 41.3% IACS, 41.6% IACS, 41.8% IACS, 412% IACS, etc.), and finally an Al-Cu-Mg alloy thick plate resistant to high stress corrosion is obtained.
[0047] The preferred embodiments of the present invention are described in detail below. The following embodiments and comparative examples are only used to illustrate the present invention, but they cannot limit the protection scope of the present invention.
[0048] Example 1
[0049] The components and weight percentages of the Al-Cu-Mg alloy used in this embodiment are: Cu 4.0%, Mg 1.6%, Mn 0.3%, Cr 0.04%, Ti 0.02%, Fe 0.03%, Si 0.02%, Cu / Mg ratio is 2.5, and the rest is Al. The aluminum alloy ingot is homogenized at a homogenization temperature of 505°C and a holding time of 48h. The homogenized ingot is heated to 460°C and then rolled at a rolling speed of 50m / min, a final rolling temperature of 385°C, a total ingot deformation of 75%, and a deformation of 5% per pass. The hot-rolled plate was subjected to a two-stage solution treatment, heating from room temperature to 480°C at a heating rate of 25°C / h, holding time for 1h, and then heated to 500°C at a heating rate of 10°C / h, holding time for 2h. After the solution treatment, it was quenched to room temperature. The obtained solid solution plate had a recrystallization area of 5.5% and a subgrain boundary density of 179mm / mm 2 The solid solution state plate is pre-stretched and cold deformed to reduce the residual stress of the plate. The plate after cold deformation is artificially aged within 30 days, with a heating rate of 10℃ / h, a holding temperature of 200℃, and a holding time of 15h.
[0050] Example 2
[0051] The components and weight percentages of the Al-Cu-Mg alloy used in this embodiment are: Cu 4.0%, Mg 1.4%, Mn 0.6%, Cr 0.03%, Ti 0.02%, Fe 0.02%, Si 0.02%, Cu / Mg ratio is 2.86, and the rest is Al. The aluminum alloy ingot is homogenized at a homogenization temperature of 505°C and a holding time of 36h. The homogenized ingot is heated to 480°C and then rolled at a rolling speed of 100m / min, a final rolling temperature of 389°C, a total deformation of the ingot of 75%, and a deformation of 25% per pass. The hot-rolled plate was subjected to a two-stage solution treatment, heating from room temperature to 480°C at a heating rate of 35°C / h, holding time for 1h, and then heated to 500°C at a heating rate of 15°C / h, holding time for 1h. After the solution treatment, it was quenched to room temperature. The obtained solid solution plate had a recrystallization area of 7.9% and a subgrain boundary density of 165mm / mm 2 The solid solution state plate is pre-stretched and cold-deformed to reduce the residual stress of the plate. The plate after cold deformation is artificially aged within 30 days, with a heating rate of 15℃ / h, a holding temperature of 220℃ and a holding time of 10h.
[0052] Example 3
[0053] The components and weight percentages of the Al-Cu-Mg alloy used in this embodiment are: Cu 4.6%, Mg 1.6%, Mn 0.9%, Cr 0.02%, Ti 0.03%, Fe 0.03%, Si 0.02%, Cu / Mg ratio is 2.88, and the rest is Al. The aluminum alloy ingot is homogenized at a homogenization temperature of 510°C and a holding time of 24h. The homogenized ingot is heated to 500°C and then rolled at a rolling speed of 75m / min, a final rolling temperature of 402°C, a total deformation of the ingot of 90%, and a deformation of 15% per pass. The hot-rolled plate was subjected to a two-stage solution treatment, heating from room temperature to 490°C at a heating rate of 40°C / h, holding time of 0.5h, and then heated to 505°C at a heating rate of 18°C / h, holding time of 2h. After the solution treatment, it was quenched to room temperature. The obtained solid solution plate had a recrystallization area of 14.5% and a subgrain boundary density of 116mm / mm 2 The solid solution state plate is pre-stretched and cold-deformed to reduce the residual stress of the plate. The plate after cold deformation is artificially aged within 30 days, with a heating rate of 15℃ / h, a holding temperature of 210℃ and a holding time of 15h.
[0054] Example 4
[0055] The components and weight percentages of the Al-Cu-Mg alloy used in this embodiment are: Cu 4.5%, Mg 1.5%, Mn 0.5%, Cr 0.03%, Ti 0.03%, Fe 0.02%, Si 0.02%, Cu / Mg ratio is 3, and the rest is Al. The aluminum alloy ingot is homogenized at a temperature of 508°C and a holding time of 36h. The homogenized ingot is heated to 470°C and then rolled at a rolling speed of 75m / min, a final rolling temperature of 393°C, a total deformation of the ingot of 90%, and a deformation of 15% per pass. The hot-rolled plate was subjected to a two-stage solution treatment, heating from room temperature to 485°C at a heating rate of 50°C / h, holding time for 1h, and then heated to 505°C at a heating rate of 20°C / h, holding time for 2h. After the solution treatment, it was quenched to room temperature. The obtained solid solution plate had a recrystallization area of 11.2% and a subgrain boundary density of 140mm / mm 2 The solid solution state plate is pre-stretched and cold deformed to reduce the residual stress of the plate. The plate after cold deformation is artificially aged within 30 days, with the aging treatment heating rate of 20℃ / h, the insulation temperature of 210℃ and the insulation time of 12h.
[0056] Example 5
[0057] The components and weight percentages of the Al-Cu-Mg alloy used in this embodiment are: Cu 4.3%, Mg 1.5%, Mn 0.8%, Cr 0.03%, Ti 0.02%, Fe 0.02%, Si 0.03%, Cu / Mg ratio is 2.87, and the rest is Al. The aluminum alloy ingot is homogenized at a temperature of 508°C and a holding time of 32h. The homogenized ingot is heated to 490°C and then rolled at a rolling speed of 75m / min, a final rolling temperature of 391°C, a total deformation of the ingot of 80%, and a deformation of 20% per pass. The hot-rolled plate was subjected to a two-stage solution treatment, heating from room temperature to 485°C at a heating rate of 40°C / h, holding time for 1h, and then heated to 505°C at a heating rate of 15°C / h, holding time for 1h. After the solution treatment, it was quenched to room temperature. The obtained solid solution plate had a recrystallization area of 13.7% and a subgrain boundary density of 153mm / mm 2 The solid solution state plate is pre-stretched and cold-deformed to reduce the residual stress of the plate. The plate after cold deformation is artificially aged within 30 days, with a heating rate of 15℃ / h, a holding temperature of 210℃ and a holding time of 12h.
[0058] Example 6
[0059] The components and weight percentages of the Al-Cu-Mg alloy used in this embodiment are: Cu 4%, Mg 1.5%, Mn 0.8%, Cr 0.02%, Ti 0.02%, Fe 0.03%, Si 0.03%, Cu / Mg ratio of 2.67, and the rest is Al. The aluminum alloy ingot is homogenized at a temperature of 508°C and a holding time of 32h. The homogenized ingot is heated to 490°C and then rolled at a rolling speed of 75m / min, a final rolling temperature of 393°C, a total deformation of the ingot of 80%, and a deformation of 10% per pass. The hot-rolled plate was subjected to a two-stage solution treatment, heating from room temperature to 485°C at a heating rate of 40°C / h, holding time for 1h, and then heated to 505°C at a heating rate of 15°C / h, holding time for 1h. After the solution treatment, it was quenched to room temperature. The obtained solid solution plate had a recrystallization area of 13.9% and a subgrain boundary density of 157mm / mm 2 The solid solution state plate is pre-stretched and cold-deformed to reduce the residual stress of the plate. The plate after cold deformation is artificially aged within 30 days, with a heating rate of 15℃ / h, a holding temperature of 200℃ and a holding time of 10h.
[0060] Comparative Example 1
[0061] The components and weight percentages of the Al-Cu-Mg alloy used in this comparative example are: Cu 3.8%, Mg 1.2%, Mn 0.6%, Cr 0.03%, Ti 0.04%, Fe 0.02%, Si 0.03%, Cu / Mg ratio of 3.17, and the rest is Al. The aluminum alloy ingot is homogenized at a temperature of 508°C and a holding time of 32h. The homogenized ingot is heated to 500°C and then rolled at a rolling speed of 75m / min, a final rolling temperature of 387°C, a total deformation of the ingot of 80%, and a deformation of 20% per pass. The hot-rolled plate was subjected to a two-stage solution treatment, heating from room temperature to 480°C at a heating rate of 40°C / h, holding time for 1h, and then heated to 500°C at a heating rate of 15°C / h, holding time for 1h. After the solution treatment, it was quenched to room temperature. The obtained solid solution plate had a recrystallization area of 17.8% and a subgrain boundary density of 112mm / mm 2 The solid solution state plate is pre-stretched and cold-deformed to reduce the residual stress of the plate. The plate after cold deformation is artificially aged within 30 days, with a heating rate of 15℃ / h, a holding temperature of 210℃ and a holding time of 12h.
[0062] Comparative Example 2
[0063] The components and weight percentages of the Al-Cu-Mg alloy used in this comparative example are: Cu 4.3%, Mg 1.5%, Mn 0.2%, Cr 0.04%, Ti 0.04%, Fe 0.02%, Si 0.02%, Cu / Mg ratio of 2.87, and the rest is Al. The aluminum alloy ingot is homogenized at a temperature of 500°C and a holding time of 36h. The homogenized ingot is heated to 440°C and then rolled at a rolling speed of 75m / min, a final rolling temperature of 324°C, a total deformation of the ingot of 80%, and a deformation of 20% per pass. The hot-rolled plate was subjected to a two-stage solution treatment, heating from room temperature to 480°C at a heating rate of 40°C / h, holding time for 1h, and then heated to 500°C at a heating rate of 15°C / h, holding time for 1h. After the solution treatment, it was quenched to room temperature. The obtained solid solution plate had a recrystallization area of 24.2% and a subgrain boundary density of 69mm / mm 2 The solid solution state plate is pre-stretched and cold-deformed to reduce the residual stress of the plate. The plate after cold deformation is artificially aged within 30 days, with a heating rate of 15℃ / h, a holding temperature of 210℃ and a holding time of 12h.
[0064] Comparative Example 3
[0065] The components and weight percentages of the Al-Cu-Mg alloy used in this comparative example are: Cu 4.8%, Mg 1.6%, Mn 0.6%, Cr 0.02%, Ti 0.04%, Fe 0.02%, Si 0.02%, Cu / Mg ratio is 3, and the rest is Al. The aluminum alloy ingot is homogenized at a homogenization temperature of 495°C and a holding time of 36h. The homogenized ingot is heated to 480°C and then rolled at a rolling speed of 75m / min, a final rolling temperature of 384°C, a total deformation of the ingot of 80%, and a deformation of 20% per pass. The hot-rolled plate was subjected to a two-stage solution treatment, heating from room temperature to 480°C at a heating rate of 40°C / h, holding time for 1h, and then heated to 500°C at a heating rate of 15°C / h, holding time for 1h. After the solution treatment, it was quenched to room temperature. The obtained solid solution plate had a recrystallization area of 12.8% and a subgrain boundary density of 134mm / mm 2 The solid solution state plate was pre-stretched and cold deformed to reduce the residual stress of the plate. The plate after cold deformation was artificially aged within 30 days, with a heating rate of 15℃ / h, a holding temperature of 230℃ and a holding time of 17h.
[0066] See Table 1 for the room temperature tensile properties, electrical conductivity and stress corrosion properties of the Al-Cu-Mg alloy thick plates prepared in the examples of the present invention and the comparative examples. The stress corrosion properties of the examples in Table 1 under high stress conditions are significantly better than those of the comparative examples.
[0067] Figure 1 The homogenized structure of the aluminum alloy ingot in Example 1; Figure 2 is the grain structure of the aluminum alloy thick plate in Example 1; Figure 3 is the grain structure of the aluminum alloy thick plate in Example 2; Figure 8 The grain structure of the aluminum alloy thick plate in Comparative Example 2. It can be seen that the present invention controls the content of the microalloying element Mn and reasonably matches the hot rolling temperature, regulates the dynamic recrystallization and static recrystallization processes, and makes the final plate obtain a higher density subgrain structure, and obtains a microstructure characteristic with excellent stress corrosion resistance.
[0068] Figure 4 TEM structure of the precipitation phase in the aluminum alloy thick plate in Example 3; Figure 5 This is the TEM structure of the grain boundary precipitation phase of the aluminum alloy thick plate in Example 4. The present invention optimizes the characteristics of the intragranular and grain boundary precipitation phases by controlling the content of the main alloying elements and the Cu / Mg ratio and matching the aging treatment process, thereby achieving excellent stress corrosion resistance while ensuring strength.
[0069] Figure 6 This is a cross-sectional view of a C-ring fracture of an aluminum alloy thick plate in Example 5 of the present invention; Figure 7 This is a cross-sectional view of a C-ring fracture of an aluminum alloy thick plate in Example 6 of the present invention; Fig. 9 This is a cross-sectional view of the C-ring fracture of the aluminum alloy thick plate in Comparative Example 3 of the present invention. After the C-ring in the embodiment is soaked for 30 days under the stress condition of 370 MPa, the surface of the C-ring is mainly corrosion pits. The metallographic observation of the fracture section of the C-ring shows that the width of the corrosion pit is greater than the depth, and the stress corrosion performance is excellent; after the C-ring in the comparative example is soaked for 30 days under the stress condition of 370 MPa, long cracks appear on the surface. The metallographic observation of the fracture section of the C-ring shows that the depth of the corrosion pit is in the range of 1-2 mm, and the stress corrosion performance is unqualified.
[0070] The above are only specific application examples of the present invention and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent transformation or equivalent replacement shall fall within the protection scope of the present invention.
[0071] Table 1 Properties of the aluminum alloy thick plates of the embodiments and comparative examples
[0072]
[0073] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. An Al-Cu-Mg alloy resistant to high stress corrosion, characterized in that: The components and weight percentages are: Cu 4.0-4.6%, Mg 1.4-1.6%, Mn 0.3-0.9%, Cr≤0.06%, Ti≤0.03%, Fe≤0.05%, Si≤0.03%, the total amount of impurity elements is less than 0.15%, and the balance is Al, wherein the Cu / Mg ratio is not greater than 3.
2. A method for preparing a high stress corrosion resistant Al-Cu-Mg alloy thick plate, characterized in that: Using the Al-Cu-Mg alloy ingot as claimed in claim 1 as a raw material for making thick plates; S1: homogenizing the Al-Cu-Mg alloy ingot at a homogenization temperature of 505-510°C; S2: hot rolling the homogenized ingot to obtain a plate, when the Mn content of the alloy is less than or equal to 0.6%, the initial rolling temperature T1 is 460°C≤T1≤480°C; when the Mn content of the alloy is greater than 0.6%, the initial rolling temperature T2 is 480°C<T2≤500°C, and the final rolling temperature is greater than 380°C; the total rolling deformation is 75-90%, and the deformation of each pass during the rolling process is 5-25%; S3: performing a two-stage solid solution treatment on the hot-rolled plate, and quenching to room temperature after the solid solution treatment to obtain a solid solution state plate; S4: pre-stretching and cold-deforming the solid solution plate to reduce the residual stress of the plate; S5: The cold-deformed plate is artificially aged within 30 days. The heating rate of the aging treatment is 10-20°C / h, the insulation temperature is 200-220°C, and the insulation time is 10-15h. The final plate conductivity is not less than 41% IACS, and finally an Al-Cu-Mg alloy thick plate resistant to high stress corrosion is obtained.
3. The method for preparing a high stress corrosion resistant Al-Cu-Mg alloy thick plate according to claim 2, characterized in that: The holding time of the ingot homogenization treatment described in step S1 is 24-48 hours.
4. The method for preparing a high stress corrosion resistant Al-Cu-Mg alloy thick plate according to claim 2, characterized in that: The rolling speed in step S2 is 50-100 m / min.
5. The method for preparing a high stress corrosion resistant Al-Cu-Mg alloy thick plate according to claim 2, characterized in that: The process of the double-stage solution treatment described in step S3 is: heating from room temperature to 480-490°C at a heating rate of 25-50°C / h, keeping warm for 0.5-1h, then heating to 500-505°C at a heating rate of 10-20°C / h, keeping warm for 1-2h.
6. The method for preparing a high stress corrosion resistant Al-Cu-Mg alloy thick plate according to claim 2, characterized in that: The recrystallization area of the solid solution plate obtained in step S3 is less than 20%, and the subgrain boundary density is 100-200 mm / mm 2 .
7. An Al-Cu-Mg alloy thick plate resistant to high stress corrosion prepared by the preparation method according to any one of claims 2 to 6.
8. Use of the Al-Cu-Mg alloy thick plate resistant to high stress corrosion according to claim 7 in aerospace equipment.
Citation Information
Patent Citations
A method for improving the corrosion resistance of aluminum alloys
CN108118273B